Memory-based attentional biases survive spatial suppression driven by selection history. Issue 3 (21st April 2019) - van Moorselaar, Dirk; Theeuwes, Jan; Olivers, Christian N. L.
ABSTRACT: Information in visual working memory that is only prospectively relevant can nevertheless guide attention towards memory matching visual input. Previous studies demonstrated that such memory-based attentional biases can be modulated by top-down processing strategies. Here we examined whether attentional capture by memory matching distractors is also modulated by more implicit biases stemming from selection history. Observers performed a visual search task while holding a colour in memory for a subsequent task. Crucially, a coloured distractor in the search display not only matched the memory content half of the time, it also appeared on one location more often than on all other locations. Consistent with statistical learning having a strong impact on attentional priorities, attentional capture by the distractor was attenuated at high probability distractor locations. The additional slowing by memory matching distractors, however, was the same at suppressed and non-suppressed locations. We interpret this finding as evidence that memory-based feature biases are independent from learned spatial biases.